Fenòmens de contacte lingüístic en el lèxic disponible català de Lleida - Zapata, Maribel Serrano (Studia Romanica Posnaniensia, 2016)
This article aims to analyse the influence of Spanish on the lexicon available in Catalan. For this purpose, we examine to what extent the Catalan lexicon contains elements of Spanish and what value these units have within the data available. We have also classified language contact phenomena and we have specifically analysed the instances of loans in our corpus. In order to carry out this research, we have mainly focused on the data from the province of Lleida, obtained from 240 pre-college informants who filled out an associative survey regarding 17 centers of interest.